The GLAD Lesion: are the definition, diagnosis and treatment up to date? A Systematic Review. - Porcellini, Giuseppe; Cecere, Antonio Benedetto; Giorgini, Andrea; Micheloni, Gian Mario; Tarallo, Luigi (Acta Biomedica Atenei Parmensis, 2020)
Introduction: Although GLAD lesions are quite common, only sporadic case reports describe surgical techniques and clinical outcomes. Even if cartilage defects can result from various pathogenic mechanisms, the resulting defect has some similarities with GLAD, and its management can be a starting point to treat both types of lesion. Aim of the present study is to find a commonly accepted definition for GLAD lesions in order to understand its pathogenesis, diagnosis and possible treatments. Methods: A search of PubMed (MEDLINE) database has been performed in June 2020 to identify relevant articles including a combination of the following search terms: “GlenoLabral Articular Disruption” OR "GLAD" AND "shoulder" AND "cartilage, articular". Results: Abstract evaluation included 31 articles in the full-text review. Various studies showed that the performance of MR arthrography in the detection of glenohumeral cartilage lesions, including GLAD lesions, was moderate. Different therapeutic solutions have been described. Arthroscopic debridement of the lesion and reattachment of the labrum have been often used. In case of large articular defects, the labrum could be advanced in the cartilage defect to cover it. In case of cartilage flap with reparable margins, this could be reattached with different suture constructs. Neglected GLAD lesions following a chronic trauma or shoulder instability have not been described in literature. Conclusions: The definition of GLAD injury has changed over the time. Many authors associate this lesion with shoulder instability, with trauma in abduction and extra rotation, while Neviaser’s original definition described stable shoulders following a trauma in adduction.